The impact of Bolsa Família on women’s decision-making power - de Brauw, Alan; Gilligan, Daniel O.; Hoddinott, John F.; Roy, Shalini (Elsevier, 2014)
Conditional cash transfer programs with female beneficiaries have scope to increase women's intrahousehold decision-making power. Yet quantitative evidence is limited. We show that Brazil's Bolsa Família program has significant impacts on women's decision making, but with considerable heterogeneity in effects. In aggregate, Bolsa Família significantly increases women's decision-making power regarding contraception. This effect is driven by urban households, in which Bolsa Família also significantly increases women's decision-making power in spheres related to children's school attendance and health expenses, household durable goods purchases, and contraception use. Meanwhile, in rural households, we find no increases and possible reductions in women's decision-making power.